MILKWEED FOR MONARCHS - Van Zandt, Christine; Barajas, Alejandra (Minneapolis, MN : Beaming Books, 2024)
"This lyrical picture book looks at the lifecycle of the monarch butterfly and conveys the need to care for our planet"-- Provided by publisher.
Includes bibliographical references
Ages 4-8.
Keywords: Monarch butterfly -- Life cycles -- Juvenile literature; Milkweeds -- Juvenile literature; Monarch butterfly -- Life cycles -- Juvenile poetry